Discrete robust switched H∞ tracking state feedback controllers for lateral vehicle control. (September 2015) - Lghani, Menhour; Damien, Koenig; Brigitte, d׳Andréa-Novel
Abstract: This paper considers the robust stability, stabilization and L 2 -gain analysis of switched linear systems in the simultaneous presence of uncertain and exogenous disturbances inside subsystems. The control synthesis is performed by means of linear matrix inequalities (LMIs). The effectiveness of the proposed methods is tested and shown through lateral vehicle control application. Indeed, the simulation tests are conducted using experimental data previously recorded on a race track by an instrumented vehicle during several trials. Moreover, the stability of controlled and uncontrolled vehicle models is established by means of sideslip phase-plane criteria.